Integrating fair trade with circular economy: Personality traits, consumer engagement, and ethically-minded behavior - Kutaula, Smirti; Gillani, Alvina; Leonidou, Leonidas C.; Christodoulides, Paul (My University, 2022)
With the concept of circular economy gaining increasing momentum, its connection to consumer behavior, particularly focusing on fair trade, has been relatively unexplored. Building on cognitive-affective personality system theory, we examine the role of consumer personality traits as drivers of fair trade engagement and its subsequent impact on ethically-minded behavior concerning circular economy issues. Adopting a mixed-method approach, comprising a quantitative survey among 323 consumers in the UK and India and a qualitative study among 18 British consumers, we found that extraversion, agreeableness, and conscientiousness positively affect consumer fair trade engagement, whereas neuroticism has a negative effect, and openness has no significant impact. Consumer fair trade engagement was subsequently revealed to positively influence ethically-minded behavior related to circular economy. The association between consumer fair trade engagement and ethically-minded behavior was stronger in older, more educated, and high-income consumers, whereas gender had no moderating role.
Keywords: Circular economy; Consumer engagement; Consumer ethics; Fair trade; Personality traits